2009
DOI: 10.1093/humrep/dep289
|View full text |Cite
|
Sign up to set email alerts
|

IVF outcome in patients with orthotopically transplanted ovarian tissue

Abstract: IVF in women with orthotopically grafted frozen-thawed ovarian tissue involves a higher risk of empty follicles, abnormal or immature oocytes, and low embryo transfer rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
75
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(82 citation statements)
references
References 37 publications
4
75
1
2
Order By: Relevance
“…Furthermore, extensive investigations on the effects of cryoprotectants on both human and animal ovarian tissue have not revealed any potential side effects. However, studies in women who had frozen-thawed ovarian tissue transplanted have revealed that follicles developing in the transplanted ovarian tissue are more often without oocytes and that the in vitro fertilization (IVF) pregnancy rate is relatively low compared to standard IVF patients [5,6]. Additionally, the ovarian tissue is often transported close to zero degrees for up to 24 h, which of course is not the case of mature oocytes and embryos.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, extensive investigations on the effects of cryoprotectants on both human and animal ovarian tissue have not revealed any potential side effects. However, studies in women who had frozen-thawed ovarian tissue transplanted have revealed that follicles developing in the transplanted ovarian tissue are more often without oocytes and that the in vitro fertilization (IVF) pregnancy rate is relatively low compared to standard IVF patients [5,6]. Additionally, the ovarian tissue is often transported close to zero degrees for up to 24 h, which of course is not the case of mature oocytes and embryos.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, laparoscopy and general anesthesia are required, inducing a delay of 2-6 weeks in starting CT. Importantly, the efficacy of these treatments in patients > 40 years of age seems to be uncertain [83].…”
Section: Preserving Fertility In Breast Cancer Patientsmentioning
confidence: 99%
“…Few experimental studies have tested the human ovarian tissue from both HL or NHL and failed to show evidence of ovarian involvement by lymphoma cells [18,20,24,25]. To date, 15 auto-transplantations have been reported in HL patients and 6 in NHL without any disease recurrence, knowing that the follow-up after autotransplantation in one of the HL patients is now up to 8 years [19,[26][27][28][29][30][31][32][33][34]. Nevertheless, a recent case-report showed an ovarian involvement in the histologic examination of ovarian cortex pieces in a stage III HL [15].…”
Section: Discussionmentioning
confidence: 99%